Prevalence of Enteroparasitism in Pregnant Women at the “Dr. Armando Castillo Plaza” Maternity Center, Maracaibo, Venezuela - Ellen Acurero; Iris Díaz; Nelly Díaz; Angela Bracho; María Ferrer; Alberto Matheus (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2008)
For to determine the prevalence of intestinal parasites in pregnant women between 14 and 43 years old at Dr Armando Castillo Plaza maternity center in Maracaibo Municipality. 120 stool samples were obtained and analyzed by copro-parasitical methods such as fresh test with saline solution and lugol, and concentration techniques with formaldehyde - eter (Ritchie); Kinyoun coloration for the diagnosis of intestinal coccidios. Kato Katz method was performed demonstrating the geohelminthiasis severity. Parasite infestation prevalence was found in 65.9% and the most affected age group was the one between 23 and 31 years (48.1 %), with protozoal predominance (86%) over helminth (14%). The principal parasitical species found were B. hominis (48.3%), E. nana (25%), E. coli, E. histolytica / E. dispar complex (13.3%), T. trichiura (4.2%), A. lumbricoides (3.3%), S. stercoralis (1.6%), Ancylostomideos, Taenia sp. (0.8%). No intestinal coccidios were found in any of the analysis did not demostrate any significance between the variables parasitism - group by age, parasitism - pregnancy state and parasitism - anemia. The studied pregnant population is susceptible to be infested by intestinal parasites.